The Relationship Between Knowledge And Consumption Of Fe Tablets With The Incidence Of Anemia In Adolescent Girls At Madrasah Aliyah Al-Mu'awanah Sidoarjo District - Nabila Putri Octavia; Alfi Maziyah; Tanty Wulan Dari; Loetfia Dwi Rahariyani (Global Ten Public Health and Nursing Journal, 2025)
Anemia occurs when the number of erythrocytes is below the standard value, resulting in less blood carrying oxygen supply to all body tissues. Iron deficiency leads to blood loss. One of the preventive measures is taking blood supplement tablets, but knowledge and consumption of Fe tablets are still relatively low. The study aims to analyze the relationship between knowledge and consumption of Fe tablets with the incidence of anemia in adolescent girls at Madrasah Aliyah Al-Mu'awanah Sidoarjo Regency. The cross-sectional study was conducted in March 2025 involving 40 female respondents, selected by purposive sampling. Data on knowledge and consumption of Fe tablets were obtained from a questionnaire, while the examination of hemoglobin levels was measured using the Easy Touch Glucose Cholesterol Hemoglobin tool. The results showed that 60% of respondents had good knowledge, 60% regularly consumed Fe tablets, and 62.5% were not anemic. Statistical test analysis was significant, namely the relationship between knowledge and the incidence of anemia (p = 0.000) and Fe tablet consumption with the incidence of anemia (p = 0.046). In conclusion, increasing good knowledge and consuming Fe tablets tends not to be anemic. Therefore, there is a need for continuous health education and routine health monitoring on an ongoing basis.